Effects of lanreotide autogel immediately after a single injection for thyrotropin-producing pituitary tumor - Mayuko Sumitomo; Arina Miyoshi; Shuhei Baba; Hajime Sugawara; Shinji Obara; Norio Wada (Endocrinology, Diabetes & Metabolism Case Reports, 2025)
We present the case of a 51-year-old man who was referred to our hospital due to abnormal thyroid function tests. Laboratory evaluations showed elevated serum free (F) T3 and free (F) T4 levels (9.05 pg/mL and 4.21 ng/dL, respectively), with a normal serum thyroid-stimulating hormone (TSH) level of 1.49 μIU/mL, indicating central hyperthyroidism. An 18 × 17 × 14 mm T1-weighted hypointense tumor was found on the left side of the pituitary gland, with low contrast enhancement during a cranial MRI. The TRH stimulation test revealed no TSH response. The administration of a single dose of octreotide reduced TSH levels. Following these findings, the patient was clinically diagnosed with a TSH-producing pituitary tumor (TSHoma). The patient was directed to our hospital’s neurosurgery department for pituitary surgery and began preoperative treatment with lanreotide autogel (90 mg, subcutaneous injection). Four days after administration, FT3 and FT4 levels returned to normal. Seven days after administration, an MRI revealed a 50% reduction in tumor volume. Endoscopic pituitary surgery was performed 15 days after the initial administration and resulted in complete tumor resection. A histopathological examination confirmed the presence of a TSH-producing pituitary neuroendocrine tumor. Postoperatively, FT3 and FT4 levels stayed within the normal ranges. This case demonstrates how a single dose of lanreotide autogel not only normalized thyroid hormone levels but also resulted in rapid shrinkage of the pituitary tumor in TSHoma.